2021
DOI: 10.1007/s00425-021-03598-0
|View full text |Cite
|
Sign up to set email alerts
|

Large vs small genomes in Passiflora: the influence of the mobilome and the satellitome

Abstract: doi: bioRxiv preprint MAIN CONCLUSIONSWhile two lineages of retrotransposons were more abundant in larger Passiflora genomes, the satellitome was more diverse and abundant in the smallest genome.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 99 publications
(107 reference statements)
1
27
0
Order By: Relevance
“…The detailed characterisation and identification of repetitive DNA content in the two Heloniopsis species studied highlighted the relative impact of the Ty1/copia-Angela elements in their genomes, with proportions ranging from c. 21 to 26% (Table 2). Among the Ty1/copia lineages that have been identified in plants (Neumann et al, 2019), Angela elements have been reported to be abundant in other genomes, with similar proportions as found here (e.g., Passiflora, Thinopyrum; Divashuk et al, 2020;Sader et al, 2021). Such proportions are, nonetheless, lower than for other LTR-retrotransposon elements reported in some plant genomes of comparable size to those of Heloniopsis.…”
Section: Diversity and Dynamics Of Repetitive Elements In Heloniopsissupporting
confidence: 84%
See 1 more Smart Citation
“…The detailed characterisation and identification of repetitive DNA content in the two Heloniopsis species studied highlighted the relative impact of the Ty1/copia-Angela elements in their genomes, with proportions ranging from c. 21 to 26% (Table 2). Among the Ty1/copia lineages that have been identified in plants (Neumann et al, 2019), Angela elements have been reported to be abundant in other genomes, with similar proportions as found here (e.g., Passiflora, Thinopyrum; Divashuk et al, 2020;Sader et al, 2021). Such proportions are, nonetheless, lower than for other LTR-retrotransposon elements reported in some plant genomes of comparable size to those of Heloniopsis.…”
Section: Diversity and Dynamics Of Repetitive Elements In Heloniopsissupporting
confidence: 84%
“…The data provided support to the suggestion that satellite DNAs often evolve rapidly and differ considerably in abundance even in related species with little correlation with genome size ( Macas et al, 2010 ). In addition, recent research in Passiflora (1C range = 207.34–2,621.04 Mb) reported an unusually large number of satellite repeats in the species with the smallest genome, albeit at lower frequencies, leading the authors to propose that, in most species, tandem repeats have only a limited impact on the overall genome size of Passiflora ( Sader et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ml -1 4′,6-diamidino-2-phenylindole (Sigma) in 50% glycerol (Cabral et al, 2006). Four satDNA probes were used for fluorescent in situ hybridization (FISH) experiments (Sader et al, 2021) (PorSat01-161, PorSat04-1800, PorSat07-1004, and PorSat09-1200 and labeled with 5-amino-propargyl-2′deoxyuridine 5′-triphosphate and cyanine red fluorescent dye (GE Healthcare). The FISH procedure applied to mitotic chromosomes was essentially as described in Fonsêca et al (2010).…”
Section: Core Ideasmentioning
confidence: 99%
“…NGS-related bioinformatics allowed revealing either the complete set of repetitive DNA sequences, the repeatome [8], or the broad collection of satDNAs, the satellitome [9], present in eukaryotic genomes. These approaches showed surprisingly large numbers of satDNAs in eukaryotic genomes, i.e., 62 in the migratory locust Locusta migratoria [9], 129 in the Australian morabine grasshoppers of the genus Vandiemenella [10], 164 in the characiform fish Megaleporinus microcephalus [11] and 37 in the plant Passiflora organensis [12]. Bioinformatic approaches combined with fluorescence Int.…”
Section: Introductionmentioning
confidence: 99%